Development of enzyme immunoassay for quantitation of mycelial biomass in Brassica genotypes against Alternaria blight - Antara Das; Mohd Tasleem; Manoj Singh; Dinesh Pandey; Anil Kumar; Gohar Taj (Journal of Oilseed Brassica, 2026)
Brassica crops faces a major infestation of Alternaria brassicae, a causal agent of Alternaria blight. Adoptedchemical methods for controlling Alternaria infestation are ineffective and environmentally challenging. Tobypass these challenges, strategies of enhancing innate immunity of Brassica plant resistance to pathogen, orsuppression of virulence seems promising. For suppression of virulence early detection of pathogen, beforesymptom appearance is the main limitation. Efficient disease management appropriately buffered with resistancedisease programmme depends largely on the reliable identification and characterization of fungal isolate.Therefore, there is a need to develop a potential tool for immunological characterization of isolates ofA. brassicae. Polyclonal antibody against total mycelia of A. brassicae was generated to develop ELISAbased method for early detection and quantitation of mycelial biomass. Total protein was extracted frompathogen inoculated Brassica leaves (Varuna and PAB 9511) during different time interval of infection. Thequantitative estimation of mycelial biomass of A. brassicae was estimated by indirect ELISA using polyclonalantiserum. When compared with healthy control, pathogen was not detected in the susceptible cultivar Varunauntil after 6 h of post-inoculation. It was also observed that among the inoculated genotypes of Brassica,mycelium biomass was increased with disease progression in susceptible cultivar (Varuna), while the tolerantcultivar (PAB 9511) contained less. This demonstrated the efficacy of adopted immunological technique as apotent tool for detection, quantitation of mycelial biomass for characterization of differential tolerance againstAlternaria blight in Brassica genotypes.